Chapter 1 Civic and political engagement among youth: Concepts, forms and factors - Barrett, Martyn (Taylor & Francis, 2019)
What exactly is civic and political participation? What factors influence young people's participation? How can we encourage youth to participate actively in their own democracies? Youth Civic and Political Engagement takes a multidisciplinary approach to answering these key questions, incorporating research in the fields of psychology, sociology, political science and education to explore the issues affecting youth civic and political engagement. Drawing on evidence that has been obtained in many different national contexts, and through multinational studies, this book provides a theoretical synthesis of this large and diverse body of research, using an integrative multi-level ecological model of youth engagement to do so. It identifies unresolved issues in the field and offers numerous suggestions for future research. Youth Civic and Political Engagement is an invaluable resource for researchers, teachers, youth workers, civil society activists, policymakers and politicians who wish to acquire an up-to-date understanding of the factors and processes that influence young people's civic and political engagement, and how to promote youth engagement.